Evaluasi Pembelajaran Bangun Ruang Sisi Datar Berbasis Pendekatan Konkret Pada Siswa Kelas II SDN 4 Palangka Raya Program Studi Pendidikan Guru Sekolah Dasar - Inul Dara Miska; Juwita Oktaviana; Natazya Clara Zalianty (CV. ITTC INDONESIA, 2026)
This study aims to evaluate the understanding of second-grade students at SDN 4 Palangka Raya regarding flat-sided spatial figures, especially cubes and rectangular prisms. This research used a descriptive qualitative approach with 14 students as the subject. Data were collected through written evaluation tests and classroom observations during learning activities. The results showed that most students were in the good category in understanding the shapes, characteristics, and elements of spatial figures. The use of concrete objects such as cartons and boxes helped students understand abstract material more easily. However, some students still had difficulty in counting edges and vertices. These findings indicate that concrete learning can improve students’ understanding of flat-sided spatial figures.